Implementasi Android Sebagai Web Server Online Dengan Virtual Private Network - Sigit Sugiharto; Supriyanto, Supriyanto; Rozaq Isnaini Nugraha (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Android is an operating system whose capabilities continue to increase from year to year. The capabilities of Android currently match the capabilities of a computer. Not only limited to ordinary computers, what a server computer can do can now be done on Android, including making Android a web server. So it is possible for people who have Android to have their own web server. The problem that arises is that the web server on Android cannot be accessed directly via the internet. Cellular operators do not provide Public IP to their customers, so a way is needed so that the Android web server can be accessed on the internet, one of which is by using Virtual Private Network (VPN) technology. The aim of this research is to make the web server on Android accessible on the internet. The method used is to combine a Virtual Private Server (VPS) and Android using VPN. The research results showed that VPN can be a bridge so that the web server on Android can be accessed from the internet.